Yearbook of the International Court of Justice 2021-2022 - International Court of Justice (United Nations, 2024)
The bilingual Annuaire-Yearbook 2021-2022 presents the work of the International Court of Justice between 1 August 2021 and 31 July 2022, as well as its organization and functioning.